The Role of Socio-Cultural on Online Learning Performance: The Role of Students’ Experience - Harmita Sari; Ming-Chou Liu; Anshari Anshari; Chen Ching Yang; Altri Wahida; A. Nurhayati (Universitas Cokroaminoto Palopo, 2024)
This research investigates how socio-cultural learning process influences students’ experience during and after the COVID-19 pandemic which subsequently influencing their E-Learning performance. 320 valid respondents were recruited for an online survey study. Structural Equation Modeling (SEM) was used to test the research hypotheses. This study found that socio-cultural learning has a crucial role in students’ experience. However, social-cultural Learning has a greater effect on students’ experience. Furthermore, mediator variables, students’ experience, partially mediate therelationship between socio-cultural learning and E-Learning performance. The result of the current study contributes to extend literature education field toward socio-cultural and E-Learning simultaneously. It also develops a new view into the determinants factor to influence students’ experience.